Tinjauan Hukum Islam atas Problematika Larangan Perkawinan Beda Suku di Nagari Guguak Malalo Sumatera Barat - Elva Mahmudi (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2022)
This study examines the practice of prohibiting inter-ethnic marriages in Nagari Malalo. An ethnographic approach will look at how Islamic law reviews the practice of prohibiting inter-ethnic marriages that occur, and what sanctions are applied to people who violate the prohibition. This type of research is a field research, where to obtain data from the problems studied, the authors conduct observations and in-depth interviews with credible sources determined purposively. The processing of the data obtained is done in a descriptive-qualitative way. As a result, the prohibition of marriage between different ethnic groups, consists of two classifications, namely; (1) prohibition of marriage between different tribes in one Koto and. (2) prohibition of marriage between different ethnic groups between Koto. Meanwhile, Islamic law has explained in detail who is prohibited from marrying. And the prohibition of marriage between different ethnic groups is not part of this provision. However, this does not mean that the prohibition against inter-ethnic marriage is contrary to the rules of syara'. Because the customary prohibition does not cancel the existence of the marriage and the legal consequences of marriage. In fact, the customary prohibition aims to strengthen the friendship within their people so that any problems encountered in the future can become a shared responsibility. Therefore, the custom can be said to be a good custom that needs to be preserved. By syara' it can be categorized as 'Urf Sahih or customary law and can be practiced.